Paris Street; Rainy Day from Caillebotte Paintings and Drawings at the Art Institute of Chicago - Groom, Gloria (Art Institute of Chicago, 2015)
Groundbreaking conservation and research discoveries about Caillebotte's remarkable and beloved painting Paris Street: Rainy Day are revealed in this entry from Caillebotte Paintings and Drawings at the Art Institute of Chicago. One of the many digital assets included in the catalogue is a video shot on the street in Paris that helps to explain the artist's use of a camera lucida to create the preparatory sketch and painting. Interactive and layered high-resolution imaging, videos, and previously unpublished technical photography unveil extensive new research on Paris Street: Rainy Day. For the full catalogue, please visit www.artic.edu/digitalcaillebotte